2021
DOI: 10.1002/cncr.33789
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of adavosertib (AZD1775) in combination with concurrent radiation and cisplatin for intermediate‐risk and high‐risk head and neck squamous cell carcinoma

Abstract: Background Adavosertib (AZD1775) is an inhibitor of the Wee1 kinase. The authors conducted a phase 1b trial to evaluate the safety of adavosertib in combination with definitive chemoradiotherapy for patients with newly diagnosed, intermediate‐risk/high‐risk, locally advanced head and neck squamous cell carcinoma (HNSCC). Methods Twelve patients with intermediate‐risk/high‐risk HNSCC were enrolled, including those with p16‐negative tumors of the oropharynx, p16‐positive tumors of the oropharynx with ≥10 tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In contrast, it enhanced the cytotoxic effect of CompC in Renca cells ( Figure 5 c). Previously, the combination of Adavo with various DNA-damaging agents, including 5-fluorouracil, cisplatin, and radiation, has been reported to produce robust anti-tumor activity [ 46 , 47 ]. Adavo enhances the cytotoxic effects of 5-fluorouracil in p53-deficient human colon cancer cells, presumably by premature entry into mitosis via inhibition of Cdk1 Tyr 15 phosphorylation, induction of histone H3 phosphorylation, abrogation of DNA damage checkpoints, and G2 block [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it enhanced the cytotoxic effect of CompC in Renca cells ( Figure 5 c). Previously, the combination of Adavo with various DNA-damaging agents, including 5-fluorouracil, cisplatin, and radiation, has been reported to produce robust anti-tumor activity [ 46 , 47 ]. Adavo enhances the cytotoxic effects of 5-fluorouracil in p53-deficient human colon cancer cells, presumably by premature entry into mitosis via inhibition of Cdk1 Tyr 15 phosphorylation, induction of histone H3 phosphorylation, abrogation of DNA damage checkpoints, and G2 block [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these promising studies, further phase 1 studies have investigated the combination of certain anticancer agents in specific types of cancers. In locally advanced or unresectable pancreatic cancer, adavosertib was combined with gemcitabine and radiation therapy at various doses [106], and in locally advanced head and neck cancer, it was combined with concurrent chemoradiation therapy with cisplatin [107]. Both studies demonstrated good drug tolerability with encouraging clinical outcomes for this strategy, suggesting that further studies should be conducted on adavosertib in combination with chemotherapy and radiotherapy.…”
Section: Wee1 Inhibitorsmentioning
confidence: 99%
“…Importantly, several preclinical studies in mice also showed increased tumor delay when radiation was combined with Wee1 inhibition (55,(85)(86)(87)(90)(91)(92)(93) and several clinical trials are currently examining the efficacy of AZD1775 with radiation therapy (sometimes in combination with chemotherapy). Phase I trials produced promising results (94,95), although the combination with cisplatin prompted the need for toxicity-related dosing adjustments (95). The initial proposal that p53 status was an essential biomarker for the radiosensitization by Wee1 inhibition (55) was put into doubt by subsequent studies (89).…”
Section: Radiosensitization By Wee1 Inhibitionmentioning
confidence: 99%